St. Maximus the Confessor’s Contribution to the Problem of Transcending the Createdness - Vasiljević, Maksim (Sabornost - The Theological Year-book, 2012)
The topic of true being represents the fundamental aspect of theology. Theology is not primary concerned with the question of whether God (as a True Being) exists or not; its subject matter is rather how (in what manner or mode) He exists. In order for the created “being” to receive the salvific, Trinitarian mode of existence, freed from corruption and death, it is important for this being to have a corresponding relationship with Him, to actually participate in God. In the following section, we shall review the “contingency” concept (of the conditional and uncertain status) of human existence, and following that, we shall attempt to investigate the endeavor toward freedom from necessity, which is implied by the fact of having been created. The essential questions that should be asked here are the following: Is man as we know and experience him “man”? What does “redemption” mean according to the understanding of St. Maximus, that is, what is man redeemed from? What are the assumptions (the measures, boundaries or laws) that pertain to man’s participation in the realization of his “existence”, based on the existence model of the Triune God? How can man’s ability and/or weakness in his quest for a personal communion with God within the boundaries of historical “events” be defined? For this purpose, we shall not examine the content of participation, but rather the ability of the participant–recipient. A discussion of these questions is crucial to the understanding of the anthropology of Saint Maximus the Confessor; it should be noted that on this occasion we will omit the discussion of his Christology and Ecclesiology.
Keywords: cause; weakness; being; ability; communion; participation; St. Maximus the Confessor